Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Matematika pada Siswa Kelas IV SD IT Jumalullail Belinyu - Fika Jariana; Diana Pramesti; Dodi Pranata (Universitas Muhammadiyah Bangka Belitung, 2026)
This research was conducted based on the problem of low student motivation in mathematics learning, which affects students’ critical thinking and problem-solving abilities as well as their active participation in classroom activities among sixth-grade students at SD IT Jamalulail Belinyu. The purpose of this study was to improve students’ mathematics learning outcomes through the implementation of the Problem-Based Learning (PBL) model. This study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The research subjects consisted of 25 students. Data were collected through interviews, observations, and tests. The instrument was tested for validity and reliability, followed by normality and paired-sample t-tests. The normality test using the Shapiro-Wilk method in SPSS indicated that the data were normally distributed, with significance values of 0.149 for the pretest and 0.052 for the posttest, both exceeding 0.05. The results of the paired-sample t-test showed a significance value of 0.000 (p < 0.05), indicating that the Problem-Based Learning (PBL) model had a significant effect on improving students’ mathematics learning outcomes.